Molecular Docking of Benzimidazole Derivative Compounds as Xanthin Oxidase Inhibitor - Dewi, Tanaya Jati Dharma; Muttakin, Muhammad Zaki; Azzahra, Rani; Fuadah, Arti Septina Nur; Annaura, Syifa; Faiza, Nahda Aqila (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2023)
Modifying the structure of a compound can increase the potency and selectivity of a compound. In designing a compound that is potent and selective, this can be done by: several methods, one of which is molecular docking. Benzimidazole, a special organic compounds with N-heterocyclic ring systems show various biological activities through effective binding to enzyme receptor sites. xanthin oxidase is one of the target proteins which is an enzyme. This study aimed to predict benzimidazole derivate compounds as  xanthin oxidase inhibitor using molecular docking and predict their physicochemical properties. Molecular docking menggunakan Molegro Virtual Docker, for physicochemical properties using SwissADME.  The results of the research showed that the activity of Benzimidazole derivative compounds is better than Allopurinol, whic is shown from the Rerank Score value which is lower than allupurinol so that the activity of the Benzimidazole derivative compound as a Xanthin Oxidase receptor inhibitor is better and more stable as a new drug candidate.